Pesticide chemistry : (Wiley-VCH, 2007)
This book deals with modern crop protection -- covering science, technology, regulation and economical issues.The book consists of about 50 works selected from the forum for pesticide development and use cover key aspects in modern pesticide chemistry and technology, including agriculture, agrochemicals, and environmental health aspects, as well as global issues, such as food quality and safety. This comprehensive volume even captures such emerging technologies as crop protection and production, genomics, proteomics, and metabolomics.